Capturing Shadows of the Wars: Memories of Camp Town Women in South Korea and Japan. (2nd January 2021) - Jang, Nayun
Abstract : This essay examines lens-based artworks in South Korea and Japan, focusing on the ways in which artists challenge official memory by drawing attention to the lives of women in U.S. military camp towns. Both countries witnessed growing presence and activities of U.S. military in the aftermath of the Asia-Pacific War and the Korean War, but the overwhelming impact of Americanisation in ordinary people's lives has been neglected in the formation of nationalistic official memories. Highlighting the lens-based artists' role as creators of "counter-memory", which represents "individual's resistance against the official versions of historical continuity", the essay analyses their artistic attempts to make sense of and overcome the troubled past by means of memory.